Leveraging Instagram for Nonprofit Growth: A Digital Marketing Strategy for Ruang Belajar Aqil - Safira Rusyda Azizah; Rayie Tariaranie Wiraguna; Della Ayu Zonna Lia; Meirna Puspita Permatasari; I Made Ariana; Nikita Amalia (Yayasan Sembilan Pemuda Indonesia, 2026)
In the rapidly shifting digital landscape, nonprofits like Ruang Belajar Aqil (RBA) face the dual challenge of sustaining social impact while mastering platforms such as Instagram to foster engagement, visibility, and organizational growths. An effective marketing approach enables nonprofits to articulate the social value of their activities, attract support from donors, volunteers, partners, and build trust among participants regarding the benefits provided. This study aims to design and implement a visual identity (mood board) and a six-month content plan for Ruang Belajar Aqil (RBA), a nonprofit in Malang Indonesia, to strengthen its branding and online engagement. This research using a qualitative approach, including Focus group Discussion (FGDs), interviews, direct observation, social media audits, and the use of secondary data. The study resulted in a strategic framework that enhances visual consistency, improves audience engagement, and supports Ruang Belajar Aqil (RBA) sustainability. Therefore, the development of a mood board and a six-month content plan is proposed as a strategic initiative to enhance the branding and visibility of the nonprofit organization Ruang Belajar Aqil. This approach is expected to strengthen its public image and significantly contribute to its growth and sustainability. This offers a replicable model for other resource-constrained nonprofits.